Experimental measurements and modeling of supercritical CO2 adsorption on 13X and 5A zeolites - Abdul Kareem, F.A. (Elsevier B.V., 2018)
In this work, critical and supercritical operating conditions for CO2 removal studies had been inspected on 13X and 5A Zeolites in terms of CO2 adsorption, at 150 bars and two different operating temperatures, 50 and 70 Â°C. The newly developed and very high accuracy (10â6 precision) setup which consisted of gravimetric measurements was used to study the static adsorption. Excess isotherms had been corrected (Absolute/Gibbs isotherms) and measured. 13X zeolite showed higher adsorption which was 330 mg/g at 50 Â°C and 300 mg/g at 70 Â°C for CO2 at supercritical conditions, compared to 5A zeolite 280 mg/g, 230 mg/g, respectively. The absolute isotherms for both adsorbents are further predicted and simulated via artificial neural network (ANN) modeling. However, the predicted and simulated isotherms showed high agreement and consistency to the experimental data, respectively. Results for both adsorbents were fitted to the most favorable equilibrium models, namely Langmuir, Freundlich, Toth, and Sips isotherm. The results showed high acceptance (R2 0.999) for Langmuir and Toth, especially at higher pressure. Virial curves and coefficients had been used to identify the Isosteric Heat of adsorption for 13X and 5A zeolites at the operating temperatures and pressure range. The curves illustrated that 5A started to saturate faster than 13X. The fluidical density of CO2 was observed at 0.7070 g/cm3 and 0.5054 g/cm3 on 13X at 50 and 70 Â°C respectively, and 13X had a higher fluidical density of CO2 compared to 5A. 13X and 5A zeolites showed lower rate constants at 70 Â°C compared to the values at 50 Â°C. The kinetic rate constant i.e.: k â 0.0098 at 50 Â°C and 0.0013 at 70 Â°C on 13X, and k â 0.0026 at 50 Â°C, and 0.0021 at 70 Â°C on 5A were observed at 150 bar. Â© 2017 Elsevier B.V.